2008
DOI: 10.1007/s12010-008-8432-8
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis and Fermentation of Pretreated Cashew Apple Bagasse with Alkali and Diluted Sulfuric Acid for Bioethanol Production

Abstract: The aim of this work was to optimize the enzymatic hydrolysis of the cellulose fraction of cashew apple bagasse (CAB) after diluted acid (CAB-H) and alkali pretreatment (CAB-OH), and to evaluate its fermentation to ethanol using Saccharomyces cerevisiae. Glucose conversion of 82 +/- 2 mg/g CAB-H and 730 +/- 20 mg/g CAB-OH was obtained when 2% (w/v) of solid and 30 FPU/g bagasse was used during hydrolysis at 45 degrees C, 2-fold higher than when using 15 FPU/g bagasse, 44 +/- 2 mg/g CAB-H, and 450 +/- 50 mg/g C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 21 publications
4
33
1
1
Order By: Relevance
“…The literature reports a relative efficiency in the association of these two processes. In an acidic pretreatment to delignify cashew bagasse, approximately 75% of mass yield was achieved after pretreatment with low sulfuric acid concentration (0.8 mol L -1 ) and C alkali of about 4%, for 1 hour and at 100°C (ROCHA et al, 2009). When cashew bagasse was pretreated with 0.5 to 3.5% of acid and 1.5% of alkali, glucose conversions of up to 60% were attained (ROCHA et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reports a relative efficiency in the association of these two processes. In an acidic pretreatment to delignify cashew bagasse, approximately 75% of mass yield was achieved after pretreatment with low sulfuric acid concentration (0.8 mol L -1 ) and C alkali of about 4%, for 1 hour and at 100°C (ROCHA et al, 2009). When cashew bagasse was pretreated with 0.5 to 3.5% of acid and 1.5% of alkali, glucose conversions of up to 60% were attained (ROCHA et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment with diluted sulfuric acid thoroughly hydrolyzes the hemicellulose fraction to the medium which, depending on the acid concentrations employed, also releases cellulose to a greater or lesser extent, and other components such as pectin and water-soluble proteins (CORTEZ, 2010). Contrastingly, milder operating conditions (temperature and pressure) are employed in alkaline processes whose main effect is the removal of lignin from the biomass, enhancing higher fiber reactivity (MOSIER et al, 2005;ROCHA et al, 2009). The alkali, usually soda, tends to cause the swelling of the biomass decreasing cellulose crystallinity and increasing surface area and porosity (PITARELO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PAGANINI et al (2005) observed an ethanol yield of 44% for the fermentation of apple pomace. ROCHA et al (2009) optimized the enzymatic hydrolysis of cashew bagasse previously treated by alkaline and acidic methods and obtained ethanol yields between 0.38 and 0.47g ethanol g -1 glucose. These yields are in close agreement with the results reported in the present research (0.31g ethanol g -1 ART), thus demonstrating an efficient route of enzymatic hydrolysis that showed yield of 30%, or approximately 60% if only the hydrolysis step is taken into account.…”
Section: ------------------Alkaline Pretreatment---------------------mentioning
confidence: 99%
“…In Brazil, the cashew nut harvest (2008/2009) accounted for 11% of world production, which represents more than 6 million tons of cashew [8]. However, in the Northeast, cashew agroindustry has an outstanding role in the local economy, because, in industrial processes 40% (w/w) of bagasse is normally discarded by the in-dustry [9].…”
Section: Introductionmentioning
confidence: 99%
“…Such pretreatment aimed at removing lignin and hemicellulose, reducing the crystallinity of the cellulose and increasing the porosity of these materials so as to make the pulp more susceptible to hydrolysis. Among the various options for pre-treatment, the use of dilute acid in addition to removing the selective hemicellulose produces liqueurs (prehydrolysis) with high content of pentoses and reduced lignin content [8,11].…”
Section: Introductionmentioning
confidence: 99%